Efficacy of Levucell® SB (Saccharomyces cerevisiae CNCM I‐1079) as a feed additive for weaned piglets. (18th July 2017) - ,; Rychen, Guido; Aquilina, Gabriele; Azimonti, Giovanna; Bampidis, Vasileios; Bastos, Maria De Lourdes; Bories, Georges; Chesson, Andrew; Cocconcelli, Pier Sandro; Flachowsky, Gerhard; Gropp, Jürgen; Kolar, Boris; et al.
Abstract: Levucell ® SB is a feed additive based on viable cells of a strain Saccharomyces cerevisiae marketed in three formulations: SB20 with a minimum concentration of 2 × 10 10  CFU/g viable yeast cells and SB10 ME and SB Titan, both microencapsulated forms with a minimum concentration of 1 × 10 10  CFU/g viable yeast cells. In 2014, EFSA was requested by the European Commission to re‐evaluate the product when used as a zootechnical additive in feed for sows and weaned piglets. The safety of the additive for consumers, users, the environment and target animals and its efficacy for sows was established at that time. In that instance, the FEEDAP also concluded on the potential Levucell ®  SB to improve growth of piglets based on one study where supplementation of the additive was done at the recommended dose of 2 × 10 9  CFU/kg feedingstuffs and two at 1 × 10 9  CFU/kg feedingstuffs, and considered that the effective dose was 2 × 10 9  CFU/kg feedingstuffs. Two additional feeding trials in weaned piglets receiving the additive at 1 × 10 9  CFU/kg feedingstuffs are the subject of this assessment. Due to the high mortality, one of the studies was not considered. In the remaining study, the supplementation of Levucell ®  SB to weaned piglets at 1 × 10 9  CFU/kg feed resulted in a significant improvement of feed to gain ratio. Taking into account the two trials from the initial application which showed significant effects at 1 × 10 9  CFU/kg feed, the FEEDAP Panel concludes that Levucell ®  SB has the potential to improve performance of weaned piglets when added to feed at 1 × 10 9  CFU/kg complete feedingstuffs. Results of the efficacy studies can be applied to any of the three available formulations when used to deliver the same dose.